1989
DOI: 10.1007/bf00265310
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of male sterile, triazine-resistant Brassica napus by somatic hybridization between cytoplasmic male sterile B. oleracea and atrazine-resistant B. campestris

Abstract: Fusion of leaf protoplasts from an inbred line of Brassica oleracea ssp. botrytis (cauliflower, n=9) carrying the Ogura (R1) male sterile cytoplasm with hypocotyl protoplasts of B. campestris ssp. oleifera (cv "Candle", n=10) carrying an atrazine-resistant (ATR) cytoplasm resulted in the production of synthetic B. napus (n=19). Thirty-four somatic hybrids were produced; they were characterized for morphology, phosphoglucose isomerase isoenzymes, ribosomal DNA hybridization patterns, chromosome numbers, and org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Our preliminary results indicate at least alterations mapping within a SalI fragment of 11.8 kb [see map in 33] as well as sequences flanking atp9, atp6, and cox1 regions (unpublished data). The susceptibility of the Ogura mitochondrial genome to structural changes following in vitro manipulations has also been reported by other groups employing different techniques [47,36,35,21].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our preliminary results indicate at least alterations mapping within a SalI fragment of 11.8 kb [see map in 33] as well as sequences flanking atp9, atp6, and cox1 regions (unpublished data). The susceptibility of the Ogura mitochondrial genome to structural changes following in vitro manipulations has also been reported by other groups employing different techniques [47,36,35,21].…”
Section: Discussionmentioning
confidence: 79%
“…Third, both in our evolutionary and in vitro studies we noted that most of the structural alterations of the Brassica mitochondrial genome occur at specific sites via recombination across short repeated elements. Although a number of studies have already demonstrated an increased plasticity of plant mtDNA in response to tissue culture manipulations [ 17,7,39,41,50,21,4] it is still uncertain as to whether these 'culture-induced' alterations occur systematically in all higher-plant species or whether they reflect particular culture conditions such as culture age [34] or the in vitro technique employed [23]. A study of in vitro mtDNA alterations of maize [7] has also shown that the occurrence of specific types of rearrangements (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of trade names does not imply endorsement of the products named nor criticism of similar ones omitted. and B. rapa (Schenck & R6bbelen, 1982;Sundberg & Glimelius, 1986;Robertson et al, 1987;Sundberg et al, 1987;Rosdn et al,, 1988;Jourdan et al, 1989;Yamashita et al, 1989). While sporophytic self-incompatibility (SI) is common within the diploid species and is often used in the commercial production of hybrid cultivars (Dickson & Wallace, 1986), most natural B. napus is self-compatible (SC), with some exceptions (Gemmell et al, 1989;Gowers, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…While sporophytic self-incompatibility (SI) is common within the diploid species and is often used in the commercial production of hybrid cultivars (Dickson & Wallace, 1986), most natural B. napus is self-compatible (SC), with some exceptions (Gemmell et al, 1989;Gowers, 1989). Several previous studies in the somatic resynthesis of B. napus have emphasized cytoplasmic male sterility for use in commercial hybrid production in canola (Sundberg & Glimelius, 1986;Robertson et al, 1987;Sundberg et al, 1987;Ros6n et al, 1988;Jourdan et al, 1989), yet none have explored the interaction among S-alleles in somatic hybrids of the two closely-related diploid species.…”
Section: Introductionmentioning
confidence: 99%